Professional Flash mobile development creating Android and iPhone applications - Wagner, Richard 1966- (Wiley, 2011)
This guide shows Flash and ActionScript developers how to create native applications for Android mobile devices using Flash and Flash Builder.
Print version record
Keywords: Android (Electronic resource); iPhone OS; Flash (Computer file); Application software -- Development; Mobile computing; IPhone OS; Logiciels d'application; Développement; Informatique mobile; Application software; Development